I'm a Good Mom: Enhancing Self-Esteem, Self-Efficacy, and Parenting Capacity of Incarcerated Mothers through Parenting Stress Coping Strategies at Jakarta Women's Correctional Facility - Dwi Hastuti; Fauzan Ilham Kamaluddin Syah; Suci Ramadhani; Octavia Laura; Muhammad Ramdhani Al Azraq Syah; Meta Ardiana (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
Parenting stress represents a significant concern for incarcerated mothers. The Jakarta Women's Correctional Facility implements general rehabilitation, but lacks a dedicated parenting program. I'm a Good Mom addresses this gap by improving self-esteem, parental self-efficacy, and parenting capacity through stress coping strategies. The program utilized the Parenting Inside Out alongside an Active, Innovative, Creative, Effective, and Fun Learning approach, conducted over 17 offline sessions from July to September 2023. Preparation involved interviews and observations, as well as module developments, followed by execution and evaluation, utilizing pre-tests, post-tests, testimonials, and journaling. It employed quantitative instruments, specifically Rosenberg Self-Esteem Scale, Brief Parental Self-Efficacy Scale, and Parenting Stress Scale. The findings indicated 87.5% increase in selfesteem, 28.5% improvement in self-efficacy, 66% and 126% enhancement in communication and problemsolving skills, and 225% reduction in parenting stress. The program's structured methodology and collaborative framework demonstrated effectiveness and replicability for other women's correctional facilities in Indonesia